Dendritic Cell-Based Vaccines Against Cancer: Challenges, Advances and Future Opportunities. (17th November 2022) - Fu, Chunmei; Ma, Tianle; Zhou, Li; Mi, Qing-Sheng; Jiang, Aimin
ABSTRACT: As the most potent professional antigen presenting cells, dendritic cells (DCs) have the ability to activate both naive CD4 and CD8 T cells. Recognized for their exceptional ability to cross-present exogenous antigens to prime naive antigen-specific CD8 T cells, DCs play a critical role in generating CD8 T cell immunity, as well as mediating CD8 T cell tolerance to tumor antigens. Despite the ability to potentiate host CD8 T cell-mediated anti-tumor immunity, current DC-based cancer vaccines have not yet achieved the promised success clinically with the exception of FDA-approved Provenge. Interestingly, recent studies have shown that type 1 conventional DCs (cDC1s) play a critical role in cross-priming tumor-specific CD8 T cells and determining the anti-tumor efficacy of cancer immunotherapies including immune checkpoint blockade (ICB). Together with promising clinical results in neoantigen-based cancer vaccines, there is a great need for DC-based vaccines to be further developed and refined either as monotherapies or in combination with other immunotherapies. In this review, we will present a brief review of DC development and function, discuss recent progress, and provide a perspective on future directions to realize the promising potential of DC-based cancer vaccines.